Interstitial pulmonary fibrosis: The role of angiogenic factors, the inhibitory pathways of progression - E N Popova; M V Lebedeva; A B PonomarEv; I A Popova; V V Fomin (Терапевтический архив, 2014)
AIM. To assess the role of angiogenic factors (vascular endothelial growth factor (VEGF) and endothelin-1 (ET-1) in interstitial lung diseases (ILD), such as fibrosing alveolitis, sarcoidosis. MATERIALS AND METHODS. The blood levels of endothelial dysfunction and neoangiogenesis markers (ET-1 and VEGF) were investigated in 96 patients with different clinical forms of ILD at it different stages; the found changes were compared with the clinical and morphological manifestations of the disease. RESULTS. It has been ascertained that regardless of the clinical type of ILD, there is a correlation between the blood levels of VEGF and ET-1 and the intensity of lung neoangiogenesis, the expression of VEGF by the endothelium of newly formed blood vessels, the production of angiogenic factors, the degree of endothelial dysfunction, the extent of pulmonary fibrosis, the degree of pulmonary vascular remodeling, and the severity of pulmonary hypertension. The findings suggest that the markers of neoangiogenesis play an important role in the mechanisms of ILD progression. CONCLUSION. The study of these parameters in the blood may be used to clarify the activity and prognosis of ILD.